Fostering ‘talk to learn’ in an EFL classroom - Kuei-Ju Tsai (Cogent Education)
With the idea of the ‘flipped classroom’ gaining currency worldwide, university students are given more opportunities to engage in class discussions or academic conversations. While the concept of ‘talk to learn’ is not uncommon in some cultures, Taiwan has only just begun to embrace the affordance of learner-centered class discussions. Most university students have not received systematic training to engage in academic discussions. To prepare students for the practice of learning through talking, 72 Taiwanese EFL undergraduates took part in a training session, designed to improve the quality of classroom discussions by explicit instruction of academic discussion skills with varying discussion formats (the fishbowl discussion and the regular discussion). Students’ discussions in the classroom were observed, analyzed, and compared within and across groups. Qualitative and quantitative analyses of classroom discussions showed a heightened awareness of the nature of academic discussions and improved conscious efforts to co-construct understanding, regardless of the format. The findings support a sociocultural view of ‘talk to learn’ and confirm the value of explicitly teaching EFL learners to engage in academic conversations.